(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Leaves of the plant Medinilla beddomei were extracted using Soxhlet and ultrasound-assisted extraction methods using polar solvents, acetone, and methanol to find out the extraction efficiency. The profiling of the phytoconstituents was done by LC-Qtof-MS analysis. An in vitro MTT study was used to test the antiproliferative property of M. beddomei acetone leaf extract in two breast cancer (MCF-7, MDA-MB-231) cells and a normal cell line (L929 cells). Cell migration was conducted by the scratch wound healing assay, and cell death was evaluated by the double staining method of ethidium bromide and acridine orange. The apoptotic potential of the leaf extract was examined in the cancer cell line and the observations were evaluated by flow cytometry. The findings of the studies show that ultrasound-assisted extraction using acetone as the solvent gave a better yield of phytochemicals. According to LC-Qtof-MS analysis, phytocompounds including phenolics, flavonoids, alkaloids, terpenoids, and glycosides are present in the leaf extracts. The acetone extract showed significant anticancer properties when tested against MCF-7 and MDA-MB-231 cell lines. MDA-MB-231 cells had an IC50 value of 68.27±0.83µg/ml, while MCF-7 cells had the lowest cell viability with an IC50 value of 46.19±1.58µg/ml. However, the plant extract showed negligible toxicity towards normal cells (IC50-386.12±4.07µg/ml). The acetone leaf extract of M. beddomei demonstrated a better antimetastatic effect in MCF-7 cells. Since this extract demonstrated apoptosis modulation at several stages of the MCF-7 cell cycle, it may be a promising target for medication research against breast cancer. The results of this investigation show that the acetone leaf extract of M. beddomei may have anticancer properties, and that ultrasonic extraction is a more effective method for extracting phytochemicals.